2023
DOI: 10.3390/vaccines11010131
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NS2B-NS3 Protease Inhibitors for Therapeutic Application in ZIKV Infection: A Pharmacophore-Based High-Throughput Virtual Screening and MD Simulations Approaches

Abstract: Zika virus (ZIKV) pandemic and its implication in congenital malformations and severe neurological disorders had created serious threats to global health. ZIKV is a mosquito-borne flavivirus which spread rapidly and infect a large number of people in a shorter time-span. Due to the lack of effective therapeutics, this had become paramount urgency to discover effective drug molecules to encounter the viral infection. Various anti-ZIKV drug discovery efforts during the past several years had been unsuccessful to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The benzimidazole ring of the cocrystallization ligand was sandwiched between the side chains of Ala132-Tyr161, so both of these amino acids were considered key residues. 45 The docking protocol showed that both compounds interact with the key amino acids at the active site of NS2B-NS3 protease with binding energies lower than −7.6 kcal/mol. The 9b -NS2B-NS3 complex formed a catalytic triad at the active site characterized by the presence of the His51, Asp75, and Ser135 residues, resulting in a closed conformation of the oxyanion orifice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benzimidazole ring of the cocrystallization ligand was sandwiched between the side chains of Ala132-Tyr161, so both of these amino acids were considered key residues. 45 The docking protocol showed that both compounds interact with the key amino acids at the active site of NS2B-NS3 protease with binding energies lower than −7.6 kcal/mol. The 9b -NS2B-NS3 complex formed a catalytic triad at the active site characterized by the presence of the His51, Asp75, and Ser135 residues, resulting in a closed conformation of the oxyanion orifice.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitors’ binding mode with protease was previously reported, and His51, Asp75, and Ser135 were key amino acids that participated in H-bond and hydrophobic interactions. , Especially, Ser135 played a vital role in the inhibition activity of the compound with this target enzyme. The benzimidazole ring of the cocrystallization ligand was sandwiched between the side chains of Ala132-Tyr161, so both of these amino acids were considered key residues . The docking protocol showed that both compounds interact with the key amino acids at the active site of NS2B-NS3 protease with binding energies lower than −7.6 kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular dynamics simulations have become a standard tool for the investigation of biomolecules to assess stability and flexibility. Simulations are performed of ever bigger systems using more realistic boundary conditions and better sampling due to longer sampling times to ensure the reliability of molecular docking 87 89 . In this study, re-docking and molecular dynamics simulations were completed to ensure the reliability of molecular docking.…”
Section: Discussionmentioning
confidence: 99%
“…Autodock Vina, the open-source software for docking analysis of the selected best-screen active compounds, was used 21 , 22 . The pdbqt files for the protein and ligands were created utilizing MGL tools.…”
Section: Methodsmentioning
confidence: 99%